Same Gender Erotomania: When the Psychiatrist Became the Delusional Theme—A Case Report and Literature Review - Ruzita Jamaluddin (Case Reports in Psychiatry)
Erotomania is a rare subtype of delusional disorder, whereby the affected person believes that another individual, usually someone with higher socio-economic status, is in love with them despite having little or no contact. To the best of our knowledge, this is the first published case of same gender erotomania, involving a 28-year-old single lady and a 42-year-old divorcee towards a female psychiatrist. We aimed to share the challenges experienced by the managing psychiatrist as she inopportunely became the theme of her patients’ delusion. We also reviewed and discussed recent literature on erotomania to create awareness among psychiatrists towards this rare psychiatric condition.